Assessment of Drinking Water of Bhaktapur Municipality Area in Pre-Monsoon Season - Diwakar, Jasmine; Yami, Kayo Devi; Prasai, Tista (Scientific World, 2010)
The physico-chemical and microbiological analyses of the 116 water samples from four different sources namely, public tap, well, tube well and stone spout of Bhaktapur Municipality area were done following standard techniques for water sample collection and analyses set by the American Public Health Association (1998). The pH values of all water samples were found to lie within Nepal standard. Similarly 57(49.14%), 9 (7.76%), 56 (48.28%) and 1(0.87%) of water samples were found to exceed Nepal standard value for conductivity, turbidity, iron and chloride content respectively. Hardness content of all water samples were within the standard whereas 6 (5.17%) samples crossed ammonia permissible level. The nitrate and arsenic content of all samples were found within permissible level. The bacteriological analysis of water samples revealed the presence of total coliform in 96 (82.76%) of samples. So, the study has pointed out that the drinking water quality of city water supply has not been improved and traditional sources like stone spouts and tube well water are also not free from contamination. Such circumstances are responsible for spreading water borne outbreaks. The waterborne diseases are closely related with the conditions of living and environmental sanitation in the community. So, it can be effectively controlled by appropriate water management and safe disposal of excreta. Key words: Arsenic; Coliform bacteria; Diseases; Iron and water quality. DOI: 10.3126/sw.v6i6.2642 Scientific World, Vol. 6, No. 6, July 2008 94-98